2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609810
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain finite element models of electrochemistry in intracochlear electrodes

Abstract: Most neural prostheses feature metallic electrodes to act as an interface between the device and the physiological tissue. When charge is injected through these electrodes, potentially harmful reactions may result. Others have developed finite element models to evaluate the performance of stimulating electrodes in vivo. Few however, model an electrode-electrolyte interface, and many do not address electrode corrosion and safety concerns with respect to irreversible reactions. In this work, we successfully deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Greater detail of the modeling used in this paper has been previously documented [12]. The methodology is briefly outlined here, with changes relevant to the current study.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Greater detail of the modeling used in this paper has been previously documented [12]. The methodology is briefly outlined here, with changes relevant to the current study.…”
Section: Methodsmentioning
confidence: 98%
“…Tissue damage may also occur by "mass action" inducing excitotoxicity in the excitable tissues if the charge delivered is beyond safe limits [4], [8], [9]. Previous works have shown that current concentrates at high curvature regions of electrode geometries, such as the crests of high perimeter electrodes [10], tips of needle electrodes [11], and the vertices of CI-like half-band electrodes [12]. Early models suggested recessing the electrode to eliminate the non-uniform current distribution on the electrode surface [5], [6], based on studies of planar disc electrodes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some conductivities are from Briaire and Frijns (2000), who refer to Finley et al (1990) and Suesserman (1992). Sue et al (2013) cite Cantrell et al (2008) as giving perilymph properties of conductance r ¼ 1420 mS/m and relative permittivity e r ¼ 78. It has been assumed that inter-species variation in these properties is insignificant.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…This ability has, for example, permitted accurate modelling of cochlear micro-mechanics (Ni et al, 2016). Electrical FEMs have been used to study the behaviour of cochlear implants (Briaire and Frijns, 2000;Choi and Wang, 2014;Saba, 2012;Sue et al, 2013;Tran et al, 2011;Tran et al, 2013). Harland et al (2015) present a very detailed model of OHC membranes.…”
Section: Introductionmentioning
confidence: 99%